2022
DOI: 10.1039/d2ra05374h
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured IrOx supported on N-doped TiO2 as an efficient electrocatalyst towards acidic oxygen evolution reaction

Abstract: N–TiO2 is synthesized and innovatively employed to support IrOx nanoparticles for boosting the OER catalytic activity, stability and catalyst utilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 65 publications
(66 reference statements)
0
9
0
Order By: Relevance
“…To be specific, the lowloading Ir catalyst (Ir/low-TiON x /rGONRs) showed a slightly improved performance compared to the Ti-free samples (Ir/rGONRs); when more TiON x was deposited on the carbon nanoribbons, the OER activities of Ir/middle-TiON x /rGONRs and Ir/high-TiON x /rGONRs can be as high as 4822 and 3220 Ag Ir The enhanced catalytic activity is attributed to the synergistic effect of SMSI between Ir and TiON x and the double contact between Ir and the carrier on both sides. The IrO x /N-TiO 2 catalyst effectively enhanced the catalytic activity for OER with an overpotential of only 270 mV to drive 10 mA•cm −2 [122]. The high activity can be attributed to the support effect of N-TiO 2 , which improved the conductivity and effectively dispersed the IrO x nanoparticles.…”
Section: Support Effectmentioning
confidence: 97%
“…To be specific, the lowloading Ir catalyst (Ir/low-TiON x /rGONRs) showed a slightly improved performance compared to the Ti-free samples (Ir/rGONRs); when more TiON x was deposited on the carbon nanoribbons, the OER activities of Ir/middle-TiON x /rGONRs and Ir/high-TiON x /rGONRs can be as high as 4822 and 3220 Ag Ir The enhanced catalytic activity is attributed to the synergistic effect of SMSI between Ir and TiON x and the double contact between Ir and the carrier on both sides. The IrO x /N-TiO 2 catalyst effectively enhanced the catalytic activity for OER with an overpotential of only 270 mV to drive 10 mA•cm −2 [122]. The high activity can be attributed to the support effect of N-TiO 2 , which improved the conductivity and effectively dispersed the IrO x nanoparticles.…”
Section: Support Effectmentioning
confidence: 97%
“…It is widely used in photocatalysis and electrochemistry. 28–30 Its application in electrocatalysis is limited by its poor conductivity; however, its conductivity can be improved by doping or coating carbon. Huang et al .…”
Section: Introductionmentioning
confidence: 99%
“…It is widely used in photocatalysis and electrochemistry. [28][29][30] Its application in electrocatalysis is limited by its poor conductivity; however, its conductivity can be improved by doping or coating carbon. Huang et al prepared a HER catalyst (TiO 2 @Co 3 O 4 ), which afforded a current density of 20 mA cm À2 at a relatively small overpotential (49 mV), a performance that was superior to that of commercially available Pt/C (20%) and those of most electrocatalysts for the alkaline HER.…”
Section: Introductionmentioning
confidence: 99%
“…[6,[24][25][26] Tin based oxide supports (SnO 2 , doped-SnO 2 : antimony doped tin oxide, indium doped tin oxide, fluorine doped tin oxide etc. ), [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] titanium-based oxide supports (TiO x , Ti n O (2-n) , doped titanium oxide), [37,[43][44][45][46][47][48][49][50] Ta 2 O 5 , [51] Nbbased oxides, [52][53][54][55] are by far the most popular metal oxide supports due to their stability under oxidative conditions, and the tunable electrical conductivity for some, and possible metal-support interactions. [6] For instance, Oh et al reported a reduced effective oxide thickness in IrO 2 /ATO as compared to IrO x /C, with an observable reduction in the Ir oxidation state as a result of charge donation from ATO to IrO x .…”
Section: Introductionmentioning
confidence: 99%